Seed germination, pollination and phenology of Gloriosa superba L. (Liliaceae) - Hassan, Md Abul; Fardous, Zannatul (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(1): ,95-98 2003 (June)